The effect of exhaustion exercise on thyroid hormones and testosterone levels of elite athletes receiving oral zinc - Kilic, M.; Baltaci, A. K.; Gunay, M.; Gökbe, l. H.; Okudan, N.; Cicioglu, I. (Neuroendocrinology Letters, 2006)
The present study aims to investigate how exhaustion exercise affects thyroid hormones and testosterone levels in elite athletes who are supplemented with oral zinc sulfate for 4 weeks. The study included 10 male wrestlers, who had been licensed wrestlers for at least 6 years. Mean age of the wrestlers who volunteered in the study was 18.70 +/- 2.4 years. All subjects were supplemented with oral zinc sulfate (3 mg/kg/day) for 4 weeks in addition to their normal diet. Thyroid hormone and testosterone levels of all subjects were determined as resting and exhaustion before and after zinc supplementation. Resting TT3, TT4, FT3, FT4 and TSH levels of subjects were higher than the parameters measured after exhaustion exercise before zinc supplementation (p<0.05). Both resting and exhaustion TT3, TT4 and FT3 values after 4-week zinc supplementation were found significantly higher than both of the parameters (resting and exhaustion) measured before zinc supplementation (p<0.05). Resting total testosterone and free testosterone levels before zinc supplementation were significantly higher than exhaustion levels before zinc supplementation (p<0.05). Both resting and exhaustion total and free testosterone levels following 4-week zinc supplementation were found significantly higher than the levels (both resting and exhaustion) measured before zinc supplementation (p<0.05). Findings of our study demonstrate that exhaustion exercise led to a significant inhibition of both thyroid hormones and testosterone concentrations, but that 4-week zinc supplementation prevented this inhibition in wrestlers. In conclusion, physiological doses of zinc administration may benefit performance.